Effect of smoking methods on microbial safety, polycyclic aromatic hydrocarbon, and heavy metal concentrations of traditional smoked fish from Lagos State, Nigeria. Issue 2 (2nd April 2016) - Adeyeye, S. A. O.; Oyewole, O. B.; Obadina, O.; Adeniran, O. E.; Oyedele, H. A.; Olugbile, A.; Omemu, A. M.
ABSTRACT: A study was carried out to investigate the effect of smoking methods on microbial safety, polycyclic aromatic hydrocarbon, and heavy metal concentrations of traditional smoked fish from Lagos State, Nigeria. One hundred samples of fresh fish were obtained from 20 different fishing communities/processing centers. The fresh fish samples were divided into two batches: The first batch was smoked with drum kiln and the second batch was immediately taken to the Fish Hatchery Unit, Federal University of Agriculture, Abeokuta for smoking with convective kiln. Laboratory analyses were carried out on the two batches for: microbiological (Coliform, Fuugi, Listeria monocytogenes, Salmonella paratyphi and Staphylococcus aureus ), polycyclic aromatic hydrocarbon and heavy metals (mercury, lead, cadmium and chromium). The results of the microbiological, polycyclic aromatic hydrocarbon and heavy metal analyses revealed that there were significant variations ( p  < 0.05) between them. LC count of fresh silver catfish, spotted tilapia, bonga shad, Nigerian tongue sole, and Guinea barracuda samples were 1.9 × 10 2, 1.7 × 10 2, 2.0 × 10 2, 2.1 × 10 2 and 2.6 × 10 2 cfu/g and their drum kiln smoked samples were 4.0 × 10, 5.3 × 10 1, 6.0 × 10 1, 12.2 × 10 1 and 7.4 × 10 1 cfu/g, respectively, while samples from convective smoking kiln contain no strain of Listeria monocytogenes . The concentrations of the six major PAHs (fluorene, anthracene, benzo [b] fluoranthene, benzo [a] anthracene, benzo [a] pyrene and benzo [ghi] perylene) in the drum-smoked fish exceeded the EU maximum level of 5.0 μg/kg for BaP permissible in smoked fish, while samples smoked by convective smoking kiln showed levels below 3.5 μg BaP/kg. The study also showed that the levels of the four heavy metals investigated in the smoked fish samples are generally below the maximum permissible levels set by World Health Organization for Hg (0.2 ppm), Pb (0.3 ppm), Cd (0.2 ppm), and Cr (0.5 ppm) and hence pose no risk to smoked fish consumers.